Correlation of Salivary Retinol Binding Protein 4 (RBP4) Levels and Periodontal Severity in Patients with Chronic Periodontitis: Life Sciences-Health - Begum, Shahinaz; B, Pratebha; Muthu, Jananni; V, Priyadharshini; K, Vineela; R, Saravanakumar (International Journal of Life Science and Pharma Research, 2022)
Pro-inflammatory cytokines play a vital role in periodontitis, obesity and chronic diseases. Retinol binding protein 4 (RBP4), a novel adipokine has been implicated as a pro-inflammatory marker in obesity and other systemic diseases. In periodontal disease, RBP4 correlated with markers of low-grade inflammation. RBP4 can directly induce the production of pro-inflammatory mediators involved in leukocyte recruitment and adherence, including vascular cell adhesion molecule-1, intercellular adhesion molecule-1 etc. The present study explores the correlation of salivary RBP4 levels with periodontal parameters, BMI, and WHR in chronic periodontitis patients. A total of 91 subjects were included. Full mouth probing depth, clinical attachment levels, and bleeding on probing, BMI & WHR were recorded. Unstimulated salivary samples were collected and analyzed for RBP4 levels. Pearson’s correlation coefficient test was done to correlate RBP4 with BMI, WHR and Periodontal parameters. Correlation between RBP 4 and BMI, WHR was negative, weak and not significant (r = - 0.016, p = 0.880; r = - 0.165, p = 0.120). Correlation between RBP4 and PPD, CAL was negative, and not statistically significant (r = - 0.076, p = 0.475; r = - 0.106, p = 0.318). In underweight Group, RBP4 values did not correlate with any of the periodontal parameters. In the normal weight group, the RBP4 values correlated with only CAL (p = 0.47). In overweight and morbidly obese group, no correlation was found between RBP4 and periodontal parameters. There is no association between RBP4, Periodontal parameters, WHR and BMI in Chronic periodontitis patients.